2013
DOI: 10.1038/srep02820
|View full text |Cite
|
Sign up to set email alerts
|

Ancient carbon from a melting glacier gives high 14C age in living pioneer invertebrates

Abstract: Glaciers are retreating and predatory invertebrates rapidly colonize deglaciated, barren ground. The paradox of establishing predators before plants and herbivores has been explained by wind-driven input of invertebrate prey. Here we present an alternative explanation and a novel glacier foreland food web by showing that pioneer predators eat locally produced midges containing 21,000 years old ancient carbon released by the melting glacier. Ancient carbon was assimilated by aquatic midge larvae, and terrestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 30 publications
4
73
1
1
Order By: Relevance
“…Furthermore, radiocarbon dating of chironomid midges and four predators, which were pitfall trapped on a 6-7-year-old ground showed that they all contained ancient carbon. The wolf spider P. trailli, had a radiocarbon age of 340 years, the harvestman M. morio 570 years, the carabid beetle N. nivalis 690 years, the carabid beetle B. hastii 1100 years and chironomid midges 1040 years [29]. Even larvae and adults of predatory diving beetles collected in young ponds had a radiocarbon age of 1100-1200 years.…”
Section: Ancient Carbon As Foodmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, radiocarbon dating of chironomid midges and four predators, which were pitfall trapped on a 6-7-year-old ground showed that they all contained ancient carbon. The wolf spider P. trailli, had a radiocarbon age of 340 years, the harvestman M. morio 570 years, the carabid beetle N. nivalis 690 years, the carabid beetle B. hastii 1100 years and chironomid midges 1040 years [29]. Even larvae and adults of predatory diving beetles collected in young ponds had a radiocarbon age of 1100-1200 years.…”
Section: Ancient Carbon As Foodmentioning
confidence: 99%
“…Their guts contained a rather compact material dominated by tiny mineral particles, but diatom algae could often be seen [29,31] (Figure 13). We assume that mineral particles were ingested accidentally when 'grazing' on biofilm.…”
Section: Terrestrial Biofilm As Foodmentioning
confidence: 99%
See 3 more Smart Citations